ANALISIS PENGARUH KEPEMILIKAN MANAJERIAL, KEPEMILIKAN INSTITUSI, LEVERAGE, TERHADAP PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY (Studi Empiris pada Perusahaan Manufaktur yang Lisning di BEI) - Nidia Elvina; Makhdalena '; Fenny Trisnawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study aims to determine the influence of managerial ownership, institution ownership, Leverage on the disclosure of Corporate Social Responsibility (CSR). This research was conducted in the mining company listed on the Indonesia Stock Exchange period 2012 until 2014 with 21 sample obtained using questionare method. The analysis technique used in this research was multiple linear regression analysis. The results showed that the managerial ownership, institusional ownwrship, leverage simultaneously affected the disclosure of CSR at 0.154. Furthermore, the results of research partially showing the managerial ownership and leverage had no significant influence on CSR, and the institution ownership had significant influence on CSR.Keywords: Corporate Social Responsibility (CSR), Managerial Ownership, Institution Ownership, Leverage